1997
DOI: 10.1097/00002508-199703000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Bias Effects in Three Common Self-Report Pain Assessment Measures

Abstract: The susceptibility to manipulation appeared constant across the three measures, a finding that highlighted the difficulties clinicians and researchers encounter in accurate interpretation of results from these measures in the absence of validity indicators. This study also emphasizes the ease with which subjects with sufficient motivation can present themselves in an untruthful and manipulative manner and can generate scores that are, on their own, difficult to distinguish from those of a group of typical chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Various techniques have been employed to elicit discoloration of temporary resins 15,[25][26][27][28][29][30][31][32][33] . Accelerated aging has been used to study the effect of a discoloration on both PMMA-based and composite resins demonstrating that clinically perceptible discoloration are likely to occur in some of the tested resins 26,27,30,32) .…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been employed to elicit discoloration of temporary resins 15,[25][26][27][28][29][30][31][32][33] . Accelerated aging has been used to study the effect of a discoloration on both PMMA-based and composite resins demonstrating that clinically perceptible discoloration are likely to occur in some of the tested resins 26,27,30,32) .…”
Section: Introductionmentioning
confidence: 99%
“…positive) features of schizotypy, and that this effect is also present in those with refined knowledge about psychosis (medical students). Thus, we should be concerned about response biases on schizotypy questionnaires that can occur in a similar self-protective direction as those reported in other domains such as pain assessment (Robinson et al, 1997), self-esteem (Forsman, 1993), and drug abuse (Carey, 2002). Although we doubt that researchers would deliberately establish a psychiatric context for participants, our experimental findings demonstrate that an individual's beliefs about the purpose of a schizotypy questionnaire can influence responding.…”
Section: Discussionmentioning
confidence: 64%
“…These observations suggest that motivation to deny salient psychiatric symptoms biases self-reported schizotypy scores, just as psychological and/or financial factors seemingly distort self-report in a personally favourable direction in other domains (e.g. pain assessment: Robinson et al (1997), self-esteem: Forsman (1993), and drug abuse: Carey 2002). In a previous study using the Chapman scales (Chapman et al, 1976;Eckblad & Chapman, 1983), Mohr and Leonards (2005) showed in French and English speaking participants that positive, but not negative schizotypy scores were lower in a group of psychology students who were informed that the questionnaire assesses traits related to psychosis as compared to a group who were informed that the questionnaire assesses traits related to creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite training and an attempt to standardize the use of scales, the physicians allocated to this group may not have correctly used these instruments (8). .…”
Section: Discussionmentioning
confidence: 99%